Desenvolvimento de manual instrucional para ensinar conceitos de igual e diferente através de Matching-to-Sample (MTS) em crianças público-alvo da educação especial - Lazzarini, Fernanda Squassoni (2018)
The education of the TEA individual is a delicate area that demands a lot of care, but if there is commitment, this individual can develop his skills, essential for satisfactory social and school inclusion. Some teaching strategies, treatments and packages developed for individuals with commitments in school repertoire are available, but ABA is the set of interventions that produce the best results. For this, the present research aims to investigate the functionality and applicability of a didactic material based on the tasks used by the Applied Behavior Analysis to aid students with ASD in regular schools where teachers are not traditionally trained to work with ABA. This material was developed in two handbooks (a) Stimulus Apostille, containing all the visual stimuli that will be used to teach a specific content and (b) Teacher's Handbook, individualized per student, where the simplified registration sheets and information the student's personal needs. To evaluate the initial repertoire of the participants, a task of choice was chosen according to the adapted model, based on the notion of network of relations between stimuli and between stimuli and responses. In this research, 3 students from the municipal school system diagnosed with ASD participated. The results showed the efficacy of the adapted task and of the teaching procedures used, and it was verified the acquisition of the concept of equal and different, in a reduced period of time.